Comparison of graft uptake by underlay and overlay technique in myringoplasty - Khuwaja, Mahwash; Sajid, Tahira; Aziz, Tabassum; Ishfaq, Umair; Khan, Azmatullah (Journal of Ayub Medical College Abbottabad, 2021)
Background: About 80% of tympanic membrane tears consequential of middle ear infections or trauma restore spontaneously. Myringoplasty is the procedure to fix the perforation which fails to heal. It is of two types; overlay and underlay techniques. In former technique graft is placed lateral to the fibrous sheet of the tympanic membrane while in underlay technique the graft is placed medial to the tympanic membrane remnant. The published success rates of underlay and overlay myringoplasty varied. This study was conducted to evaluate the effectiveness of graft uptake by underlay and overlay technique in patients undergoing myringoplasty. Methods: This randomized control trial including 80 patients was carried out at Otorhinolaryngology department of Combined Military Hospital, Rawalpindi from April 2016 to September 2017. Patients going through myringoplasty for tympanic perforations were randomly allocated into two groups. Group-A underwent underlay while Group-B underwent overlay myringoplasty. Results: The age of the patients ranged from 20 to 40 years with a mean of 29.58±5.92 years with a male to female ratio of 1.2:1. Hearing improvement was significantly higher (97.5% vs. 77.5%) in patients undergoing underlay versus overlay myringoplasty. The frequency of effectiveness in terms of graft uptake was significantly higher in patients undergoing underlay (95.0% vs. 57.5%) as compared to overlay myringoplasty. Conclusion: The underlay procedure is more effective in terms of graft uptake and lesser complications as compared to overlay myringoplasty. Keywords: Tympanic Perforation; Underlay Myringoplasty; Overlay Myringoplasty